2022
DOI: 10.1177/23727322211069312
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Language Development in Infancy: What Can We Do to Support Bilingual Families?

Abstract: Many infants and children around the world grow up exposed to two or more languages. Their success in learning each of their languages is a direct consequence of the quantity and quality of their everyday language experience, including at home, in daycare and preschools, and in the broader community context. Here, we discuss how research on early language learning can inform policies that promote successful bilingual development across the varied contexts in which infants and children live and learn. Throughou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Previous research has shown that such support measures are most likely to be effective if they are tailored to families' specific situations (for more detail, see e.g. Fibla et al, 2022). Given the often disadvantaged standing of HL-speaking communities and the fact that they are commonly overlooked or ignored by official policies, tailored support measures for HL-transmitting parents could make a particularly meaningful difference and constitute a contribution to more social justice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that such support measures are most likely to be effective if they are tailored to families' specific situations (for more detail, see e.g. Fibla et al, 2022). Given the often disadvantaged standing of HL-speaking communities and the fact that they are commonly overlooked or ignored by official policies, tailored support measures for HL-transmitting parents could make a particularly meaningful difference and constitute a contribution to more social justice.…”
Section: Discussionmentioning
confidence: 99%
“…This research has made critical contributions to understanding how children learn language, and has informed recommendations for supporting multilingualism that emphasize communicative interactions between caregivers and children as well as increasing support for multilingualism in preschool programs (Fibla et al, 2021; Hoff, 2018). Yet traditional cognitive science approaches to multilingualism also have important limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Social and political forces also influence children's opportunities for multilingualism through their effects on a family's language policies (i.e., explicitly planning the use of language within the family unit; King & Fogle, 2013). Multilingual children's early language development is largely shaped by interactions that take place within the family (Fibla et al, 2021; Hoff, 2018). Typically, immigrant parents view multilingualism as an asset for their children, because it allows them to remain connected to the parent's heritage culture and supports intergenerational communication with extended family (King & Fogle, 2013; Song, 2019; Surrain, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given the current migration patterns and socioeconomic changes around the world, it has become more common for children to learn a second language from a young age. Thus, both research and educational policy makers are interested in how this process impacts children’s socio-cognitive development [ 50 , 51 ]. One way of accommodating a second language is through bilingual education [ 52 ].…”
Section: Introductionmentioning
confidence: 99%